Modulation of Electrical Properties with Controllable Local Doping in Multilayer MoTe2 Transistors. (11th September 2020) - Ke, Yuxuan; Song, Xuefen; Qi, Dianyu; Liu, Jidong; Hao, Qiaoyan; Wang, Zhuo; Tang, Sisi; Zhang, Wenjing
Abstract: It has been found that substitutional atoms, surface modification, electrostatic gating, and contact electrode engineering can induce doping effects in 2D materials. However, the doping level, area, position, and pattern shape are not well controlled; thus, it is hard to generate high‐performance, multifunctional devices and logic circuits with these doping approaches. Here, it is found that a damage‐free, highly controllable, local doping in multilayer molybdenum ditelluride (MoTe2 ) flakes can be realized with highly controllable laser beam scanning irradiation. The doping level, area, position, and pattern shape are well controlled by adjusting parameters of the scanning laser beam. With the controllable doping, the subthreshold swing of MoTe2 ‐based transistors can be decreased by one order of magnitude, well‐matched p‐type and n‐type transports can be formed, and threshold voltages can be modulated, then a complementary inverter with ultra‐high gain ≈242 is realized, which is the highest in all reported inverters based on 2D materials. It is also found that a stable negative transconductance behavior can be created for the MoTe2 transistor by controlling doping position, then a frequency doubler is successfully demonstrated. Therefore, it is proposed that the position‐controlled local doping in multilayer MoTe2 may offer exciting application potentials in future nanoelectronics. Abstract : A damage‐free, highly controllable local doping in multilayer molybdenum ditelluride (MoTe2 ) is realized by laser scanning irradiation, and the threshold voltages, subthreshold swing, and transport in p channel for the MoTe2 ‐based field‐effect transistors can be well modulated. Ultra‐high gain, low power consumption complementary inverters, and stable frequency doublers are demonstrated using this controllable doping.